Biomass of macroinvertebrates and physicochemical characteristics of water in an Andean urban wetland of Colombia - JJ Rivera-Usme; GA Pinilla; JO Rangel-Churio; MI Castro; DL Camacho-Pinzón (Brazilian Journal of Biology)
Aquatic macroinvertebrates (AMI) play an important role in the ecology of wetlands, either by their job as regulators of the cycles of matter, as for their energy storage function represented in their biomass, which is transferred to higher trophic levels. To answer the question of how biomass of different AMI trophic guilds is related with physicochemical variables in the wetland Jaboque (Bogotá, Colombia), four samplings were achieved between April 2009 and January 2010, according to periods of rain and drought in the region. The AMI biomass values obtained were rated as of intermediate rank. No temporal but spatial significant differences were found. Apparently these spatial differences appear to be associated with variations in anthropogenic pressure, which differs in each area of the wetland. In dry months (January and August), biomass was greater and dominated by detritivores. We observed a positive relationship between the specific conductance of water and the biomass of predators and detritivores and between water temperature and the biomass of detritivores and shredders. These relationships suggest that the physical and chemical variables influence the distribution, abundance, and biomass of functional groups. The physical and chemical conditions of water exhibited spatiotemporal fluctuations related to changes in the concentration of organic matter and nutrients, which presumably were related to the affluents discharges and the high impact of local human populations.